Erosividade da chuva: distribuição e correlação com a precipitação pluviométrica de Teodoro Sampaio (SP) - Colodro, G. [UNESP]; Carvalho, M. P. [UNESP]; Roque, C. G. [UNESP]; Prado, R. M. [UNESP] (Sociedade Brasileira de Ciência do Solo, 2002)
Rainfall erosivity at Teodoro Sampaio was studied through methodology proposed by Wischmeier and Smith (1958). A set of 812 erosive individual rains was selected, from a continuum series of nineteen years of nonrecording rain gauge data, according to Wischimeier (1959), Wischmeier and Smith (1978) and Cabeda (1976) and proposed with changes by Carvalho (1987). All the selected rains were computed by the package of Cataneo et al. (1982). The rainfall erosivity factor computed was 7172 MJ mm ha-1 h-1 y-1, which is expected to occur at least once each 2.33 years, with a probability of occurrence of 42.9 %. The values of the annual erosivity indices at that site expected in the return periods of 2, 5, 10, 20, 50, and 100 years were, respectively, 6,831, 8,666, 9,877, 11,046, 12,546, and 13,675 MJ mm ha-1 h-1 y-1. The greatest annual soil loss is expected to occur between the months of October and March, as shown by the 74.0 % erosivity 45.7 % with occurring between December and February of the total annual erosivity for that period. Therefore, aiming to follow the correct soil conservation principles, the better soil conservation pratices are recommended to be established and maintained throughout that particular period of the year for an effective erosion soil loss control. A high correlation was found between the montly average erosivity index EI30 and the rainfall coefficient at that site. Therefore, the regression equation obtained allows a fair estimate of the R factor to be used for other regions where climatic conditions are similar to Teodoro Sampaio's but without available data.

Foram separadas 812 chuvas individuais consideradas erosivas de uma série contínua de 19 anos de registros de dados pluviográficos. As chuvas selecionadas foram cotadas, digitalizadas e, posteriormente, analisadas pelo programa desenvolvido por Cataneo et al. (1982). O fator erosividade da chuva, expresso pelo parâmetro EI30 médio anual calculado, foi de 7.172 MJ mm ha-1 h-1 ano-1, fator esperado no local pelo menos uma vez a cada 2,33 anos, com uma probabilidade de ocorrência de 42,9 %. Os valores anuais de erosividade de Teodoro Sampaio, esperados nos períodos de retorno de 2, 5, 10, 20, 50 e 100 anos, foram, respectivamente, de 6.831, 8.666, 9.877, 11.046, 12.546 e 13.675 MJ mm ha-1 h-1 ano-1. No semestre de outubro a março, ocorreu 74,0 % da erosividade anual, sendo 45,7 % de dezembro a fevereiro. Observou-se elevada correlação entre o parâmetro EI30 médio mensal e o coeficiente de chuva (P²/P). Portanto, a equação de regressão determinada permite que seja estimado, com boa margem de segurança, o fator R para outros locais que não disponham de dados pluviográficos, mas que, entretanto, tenham dados pluviométricos e condições climáticas semelhantes às de Teodoro Sampaio (SP).
Rainfall erosivity: its distribution and relationship with the nonrecording rain gauge precipitation at Teodoro Sampaio, São Paulo, Brazil
Keywords: período de retorno; probabilidade de ocorrência; coeficiente de chuva; fator R; fator erosividade; return period; probability of occurrence; rainfall coefficient; R factor; erosivity factor